Development, validation and evaluation of a professional resilience training module for medical interns - Roslan, Nurhanis Syazni (2021)
Medical internship is a period of structured supervised practical training after the completion of medical school. Interns face long hours, exponential knowledge growth, and at the same time saving lives of patients. This overwhelming responsibility sets the stage for them to develop mental health problems. In the alarming scenario of mental health problems, research have highlighted the role of resilience in helping individuals to thrive in adversities. This study aims to develop an evidence-based and effective training module to promote professional resilience among interns. In the development phase, the researcher adopted the mixed method triangulation study design. The researcher conducted a multi-centre cross-sectional study to examine the prevalence and predictors of burnout, depression, anxiety and stress among medical interns. The researcher then conducted an in depth interview (IDI) study to explore the enablers and barriers to resilience development in the internship training. The Professional Resilience Skills Training (Pro-ReST) module was then designed guided by the findings from the mixed method study and educational model. The researcher conducted content validation with experts related to internship training and face validation with graduated medical students. Based on the refined module, the researcher conducted a parallel single-blinded placebo controlled randomized controlled trial (RCT) and diary study (embedded mixed method study) with interns from two training hospitals over a period of 10 weeks. In Phase 1, the findings revealed a high prevalence of interns with depression, anxiety, stress and burnout symptoms. Low level of resilience and maladaptive coping strategies consistently predicted burnout, depression, anxiety and stress in the internship training. The IDI findings revealed that resilience development during internship is not only driven by tenacity, but also hardiness, growth, reflective skills and control. The Pro-ReST module that was developed based on the DEAL model (Detection, and Evaluation of stressor, Action and Learning), focused on coping skills, and had an excellent Content and Face Validity Index. In Phase 3, the RCT revealed a significantly higher resilience level, planning and lower anxiety, stress symptoms, humour, self-distraction, denial, restrain, and venting in the intervention arm as compared to the control arm. However, the module also increased self-blame coping in the intervention group. The diary study revealed that many participants were more aware of their stressors and able to evaluate their coping strategies. This study found that the Pro-ReST module is effective in enhancing resilience among interns. However, interns resilience is not the total solution to mental health problems, and best works alongside systemic intervention at the organizational level.